The stalling engine in Wirtschaftswunder-Land: Germany's economic policy challenges - Horst Siebert (Institut für Weltwirtschaft (IfW), 2002)
An Englishman once watched his first American football game. He looked intently as the team gathered into a huddle after each play. His American host asked him what he thought of the proceedings. “Not a bad sport,” remarked the visitor, “but they do seem to engage in an excessive number of committee meetings.” Maybe what is true for American football is much more typical for the German economy nowadays, where trade unions and employers' associations determine the wage rate and where round tables are used to find solutions to economic policy challenges. On the more serious side, I want to talk about some of the economic policy challenges that Germany faces. Being an optimist by nature, I would paint a rosy picture, especially when abroad. As an academic, however, I have to paint a realistic picture.
Keywords: 330; Wirtschaftspolitik; Wirtschaftswachstum; Internationaler Wettbewerb; Arbeitslosigkeit; Sozialstaat; Regulierung; Korporatismus; Deutschland